Relationship between personality traits and spontaneous coronary artery dissection risk: evidence from Mendelian randomization - Zheng, Kun; Wu, Mengdi; Wang, Junhua; Sun, Jinjin; Li, Yuqian; Wang, Peng; Zhang, Zhiyue; Pan, Xiuming; Yang, Yifeng; Li, Tianqi; Guo, Yujie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSpontaneous coronary artery dissection (SCAD) significantly contributes to myocardial infarction among young individuals. Despite the elusive nature of its etiology, empirical evidence indicates a substantial correlation between sociopsychological factors and the disorder. This investigation endeavored to discern a genetic basis for personality traits influencing SCAD susceptibility.MethodsBidirectional univariate and multivariate Mendelian randomization (MR) analyses were hereby conducted to investigate the putative causal nexus between personality dimensions and SCAD risk. Besides, data regarding SCAD and personality were extracted from expansive genome-wide association studies (GWAS), and rigorous statistical inferences were made using inverse variance weighting (IVW) and ancillary methodologies. Additionally, sensitivity evaluations were performed to bolster statistical assertions.ResultsUnivariate MR analyses indicated heightened neuroticism scores as harbingers of increased SCAD risk [Odds Ratio (OR) = 1.31, 95% Confidence Interval (CI): 1.08–1.60, P = 0.007], while other personality characteristics revealed no causal interplay with SCAD. After excluding single nucleotide polymorphisms (SNPs) confounded by extrinsic variables, the association of neuroticism scores with SCAD susceptibility persisted. These findings were further substantiated by multivariate MR analyses.ConclusionsIn summary, this study identified a significant association between genetically predicted neuroticism scores and an elevated risk of SCAD. However, additional investigation is still required to elucidate the biological underpinnings of this relationship, as well as the impact of gender, environmental influences, and other contributing factors.